Environmental policy in China: Institutional analysis of the success and failure of forest management in Heilongjiang Province / Zhang Yemo - Zhang, Yemo (2019)
Consumption of natural environment and resources often relates to economy growth of a nation. The delicate balance between economic development and environment has always been a problem of concern around the world. China is known as the world's second largest economy and developing country with the most rapid economic growth. Besides that, it faces the most critical problems in over exploitation of resources and environmental destruction. In China, Heilongjiang Province played an important role in China's forest reserves and production due to its status as a major province with huge coverage of forest. This research highlighted the main issues in reform and development of state-owned forest farms in Heilongjiang Province. Quantitative and qualitative approaches based on 202 articles related to Heilongjiang's forest policy and state-owned forest farm, 5000 questionnaires, and 100 interviews are collected and organized to explore issues in state-owned forest farms reform effort and policy implementation in Heilongjiang Province. The finding shows that the main cause to impact policy implementation is backward forest management system which is highlighted based on more than half respondents of questionnaire studies, interviews and cases from content analysis of literature. Besides that, lack of human resources, insufficient control over administrative management and worker’s poor welfare are also problems of restricting progressive development of state-owned forest farm and policy implementation. In the meanwhile, suggestions are proposed that management system reform should be based on reality and the welfare of farm staff, and provincial government should transform forest farm into an affiliated public institution to balance the relationships among farms, local forestry bureau and provincial government. In conclusion, lack of public participation has halted the progress and this poses a major threat to forest conservation initiative. In order to develop better policies to protect the environment, public participation is essential. A successful reformation has a direct impact on the framework of national environmental strategies and policies, as well as the development of China's environmental policies.